IMPLEMENTATION OF GLOBAL POSITIONING SYSTEM ON OBJECT FOLLOWING CAMERA HOLDING ROBOT BASED ON ESP32 - Lubalu, Christine Gracia; Suarjaya, I Made Agus Dwi; Wibawa, Kadek Suar (JITTER : Jurnal Ilmiah Teknologi dan Komputer, 2025)
Capturing moments through photos and videos is often challenging when done alone. Therefore, this study designs an ESP32-based robot capable of automatically following and approaching objects using GPS technology. The robot is equipped with an HMC5883 sensor for direction indication, an ultrasonic sensor for obstacle avoidance, and is controlled via a mobile application based on IoT technology using the MQTT protocol. This system enables real-time location data exchange. The robot is powered by DC motors controlled through an L298 motor shield and supported by an LM2596 step-down module for power stability. Test results show that the robot can responsively follow the user's position and automatically avoid obstacles. This research offers an alt